Pelatihan Keamanan Siber Dasar Untuk Pelajar Dan Guru Di Sekolah Menengah - Tati Suprapti; Umi Hayati; Alwan Azhar; Andi Ardiansyah (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Cybersecurity is an effort that aims to protect computer systems, networks, software, and data from various digital threats such as hacking, malware, phishing, ransomware, and other attacks that can cause both material and non-material losses. In the rapidly growing digital era, especially in educational environments such as secondary schools, awareness of the importance of cybersecurity is crucial. Students and teachers who use digital devices in the teaching and learning process are often easy targets for cyber criminals who are looking for loopholes to exploit security vulnerabilities. A basic understanding of cybersecurity needs to be instilled in students and teachers so that they can identify potential threats and implement appropriate preventive measures. This article aims to provide practical guidance in recognizing common types of cyber threats, such as phishing attacks that masquerade as legitimate sites or messages, malware that infiltrates through infected software, and ransomware attacks that encrypt data for ransom. In addition, the article also outlines a number of prevention strategies that students and teachers can implement, including the use of strong passwords, regular software updates, and managing privacy on social media. By understanding the basic concepts of cybersecurity and adopting best practices in protecting digital data and devices, it is hoped that students and teachers can reduce the risks that may arise from unsafe digital activities. Furthermore, effective cybersecurity implementation can create a safer and more conducive learning environment for all parties involved.